(x+15)+(x-23)=44

Simple and best practice solution for (x+15)+(x-23)=44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+15)+(x-23)=44 equation:


Simplifying
(x + 15) + (x + -23) = 44

Reorder the terms:
(15 + x) + (x + -23) = 44

Remove parenthesis around (15 + x)
15 + x + (x + -23) = 44

Reorder the terms:
15 + x + (-23 + x) = 44

Remove parenthesis around (-23 + x)
15 + x + -23 + x = 44

Reorder the terms:
15 + -23 + x + x = 44

Combine like terms: 15 + -23 = -8
-8 + x + x = 44

Combine like terms: x + x = 2x
-8 + 2x = 44

Solving
-8 + 2x = 44

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 2x = 44 + 8

Combine like terms: -8 + 8 = 0
0 + 2x = 44 + 8
2x = 44 + 8

Combine like terms: 44 + 8 = 52
2x = 52

Divide each side by '2'.
x = 26

Simplifying
x = 26

See similar equations:

| p-18=15 | | 23x+x^2=12 | | 2x+3=-2 | | .2=.07+x(.12) | | x+3-14x+11=3x-12-10x | | x/22+3.2=16 | | 30x+18/x=-48 | | n+23= | | x/27=35 | | 36-9x=45 | | x-36=30 | | 6a+3a-5a-b= | | x+29=12 | | x-3x-6=-x | | 12a^3+39a^2-36a= | | x+8x-2=3x | | y=1.2x-3.8 | | 100-15=2.5h | | Z/3=5/3 | | 22=3x+4 | | 50x=3 | | -48=6(a) | | 300(x)=5x-120 | | 1/6(x-20)=20 | | 5c-15=2c+7 | | x-(5/6)=4x+(1/8) | | 10x+21(x-2)=113 | | 1/x+3/x+2+6/8x+4 | | 13=m/-5 | | 7m=12 | | 15+.25=20+.05 | | 8+3k=4k-3 |

Equations solver categories